The impact of 3CM model within blended learning to students' creative thinking ability - Wahyudi Wahyudi; S.B Waluya; Hardi Suyitno; Isnarto Isnarto (OmniaScience, 2020)
Creating an enjoyable atmosphere and fostering creativity are the two most required components in learning mathematics. Hence, creativity would enable students to formulate something new. In addition, creativity is one of the most important and highest competencies in Bloom's latest taxonomy. Furthermore, it is necessary to have everyone including prospective teachers. Not only for producing products in the form of objects, but the term creative also refers to problem solving in mathematic problems. This research is conducted to obtain a detail description regarding the impact of 3CM learning model among blended learning toward the enhancement of students' creative thinking skills in mathematical problem solving. To achieve this goal, a pre-experimental design with one group pre-test post-test design pattern is chosen. Creative thinking skills are measured by test techniques and are emulated with observation techniques. Observations were performed when students worked on the test. The impact of 3CM learning with blended learning seen from test results paired sample T tests with the help of SPSS program and are emulated with close ended questionnaire techniques. The results show that the average of pre-test is 60.51 and the average of post-test is 75.96. As for the results of paired T tests is the test got sig value (2-tailed) 0.000, and hence there was a significant gap among the results of pre-test and post-test. All of these results imply that 3CM learning within blended learning is undoubtedly able to increase students' creativity in solving mathematical problems. This is due to the learning situation and activities which push students to do systematic thinking. It was started by criticizing the enchanting contextual problems, creating creative products based on particular mathematical concepts, and ended by having meaningful reflection.